Hyde Park on Hudson [videorecording (DVD)] - Michell, Roger, 1956-; Murray, Bill, 1950 September 21-; Linney, Laura; Colman, Olivia; Williams, Olivia, 1968-; West, Samuel, 1966- (Universal Studios Home Entertainment, 2013)
As Great Britain faces an imminent war with Germany, US President Franklin D. Roosevelt and his wife, Eleanor, invited the King and Queen of England for a weekend at their home in upstate New York. But during the first-ever visit of a reigning British monarch to America, international affairs must be juggled with the complexities of FDR's domestic establishment, as wife, mother, and mistresses all conspire to make the royal trip an unforgettable one.